1994
DOI: 10.1016/s0001-2092(07)63295-5
|View full text |Cite
|
Sign up to set email alerts
|

The OR Suite as a Unique Trauma Resuscitation Bay

Abstract: Trauma is the fourth leading cause of death in the United States, and trauma injuries affect more than 50 million Americans annually. Inadequate care of trauma patients can cause unnecessary patient deaths. To decrease death and disability caused by trauma, one Denver hospital developed a trauma OR based on the "Golden Hour" principle (ie, the sooner a patient receives treatment, the more likely the patient will survive). Since 1977, this hospital has performed 1,838 trauma resuscitations in the trauma OR suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…However, no study has evaluated the most appropriate configuration of the trauma unit. The membership of a trauma unit depends on the location and institution-specific circumstances [5][6][7][8][9][10][11]. Although some studies have reported that only two doctors are needed to effectively treat trauma patients [12,13], other studies have reported the need to have more than two doctors in the trauma unit depending on the severity of the patient.…”
Section: Configuration Of Trauma Unitsmentioning
confidence: 99%
“…However, no study has evaluated the most appropriate configuration of the trauma unit. The membership of a trauma unit depends on the location and institution-specific circumstances [5][6][7][8][9][10][11]. Although some studies have reported that only two doctors are needed to effectively treat trauma patients [12,13], other studies have reported the need to have more than two doctors in the trauma unit depending on the severity of the patient.…”
Section: Configuration Of Trauma Unitsmentioning
confidence: 99%
“…Rapid intervention and resuscitation reduce trauma fatalities. Resuscitating critically injured patients in ORs is an essential and integral part of all Level I and II trauma programs 3 . Rapid resuscitation of patients with multisystem injuries was advocated as early as the 1930s and has been practiced routinely since the early 1960s 4 .…”
mentioning
confidence: 99%